(untitled) (Research, Society and Development, 2024)
Syphilis is one of the most common sexually transmitted infections (STIs) in the world, caused by the bacterium Treponema pallidum. Its transmission occurs predominantly through sexual intercourse, characterizing acquired syphilis, or vertically, during pregnancy, and is then called congenital syphilis. According to data from the 2023 Syphilis Epidemiological Bulletin, the state of Pará registered, in 2022, 4,359 cases of acquired syphilis, showing that the infection remains a significant concern in the region. From this perspective, the present study aims to analyze the epidemiology of acquired syphilis in the municipalities of the state of Pará that are part of the 1st Health Region, from 2018 to 2023, in addition to proposing an educational product aimed at raising awareness and promoting preventive measures related to acquired syphilis. This is an observational, descriptive, and cross-sectional study developed based on data collection from the Notifiable Diseases Information System (SINAN). During the period analyzed, 5,016 cases of acquired syphilis were confirmed, with emphasis on 2021, which recorded the highest number of occurrences, totaling 1,095 cases. Among the municipalities surveyed, Belém had the highest number of records of the disease, accounting for 3,245 cases. The results show that the 1st Health Region of the state of Pará recorded a significant number of cases throughout the period studied. Given this, it is important to strengthen epidemiological surveillance in the region and implement educational and awareness campaigns, with the aim of promoting health and raising awareness among the population.